Aspéctos éticos e identitários do consumo cultural a Casa do Saber e suas relações com a mídia - Amorim, Tatiana Regina Gomes (2009)
The object of this dissertation is the consumption of cultural goods and its relations with the media, using Casa do Saber as a start point, an institution that offers arts, philosophy, drama, music an science courses in an extra academic space. With the objective to broach the role of media in glamorization process of the consumption of cultural goods –the theoretical concepts of Pierre Bourdieu is used in this paper – in a first part, we show how the consumption of these goods are present in the legitimation and identity’s construction process of the agents/consumers and how the valuation process occurs, which means the ethical aspects of this kind of consumption. In the second part of this dissertation we set our focus in the media and its reception of the agents/consumers. We research the aspects of the media’s production and afterward analyze its reception. In this part, we also work the aspects of production and reproduction of a “legitimate culture”, analyzing how this culture is offered an which are its definition criteria. Using a qualitative methodology for this investigation, joining the direct observation and in depth interview, we could perceive the media as more than a glamorizing instance of the consumption of cultural goods; its acts permeating the social relations in the institution and constitutes one kind of capital for the agents of this specific field.